Analisis Judge's Consideration of the Elements of State Financial Loss: Study of Decision Number: 78/Pid.Sus-Tpk/2024/PN Jkt.Pst - Arter Lukas Tulia; Christenia Gladysthea Arvita Andries (Bacarita Law Journal, 2026)
The purpose is to analyze the Judge's considerations in the Central Jakarta District Court Decision Number 78/Pid.Sus-Tpk/2024/PN Jkt.Pst regarding the element of state financial losses in Article 2 paragraph (1) of Law Number 20 of 2001 concerning the Eradication of Corruption. This research uses normative juridical methods with statutory, conceptual, and case approaches. The results showed that after the Constitutional Court Decision Number 25/PUU-XIV/2016, the element of state financial loss must be proven in actual loss, not just potential loss. However, in practice, law enforcers, especially in Decision Number 78/Pid.Sus-Tpk/2024/PN Jkt.Pst, seem to ignore this. In the Budi Said case, the defendant was found guilty even though the gold that was the object of the case had not been received factually, so that the element of state loss had not been fulfilled in reality and the actions of PT Antam Tbk were civil actions in the private sphere so that they could not be qualified as state financial losses. This journal criticizes law enforcement that pays less attention to the meaning of material offenses in corruption cases, especially related to proving state financial losses and ignoring incracht civil decisions on legal events a quo.